Investigating music algorithm in neural information processing: robust feature extraction for emotional state classification from multichannel EEG signals - Hossain, Md. Sakib Abrar (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Master of Engineering in Computer Science and Engineering, 2021.